Criteria for minimum powering and maneuverability in adverse weather conditions. Issue 3 (October 2015) - Shigunov, V.; Papanikolaou, A.
Abstract : The 2012 guidelines on the method of calculation of the attained Energy Efficiency Design Index (EEDI) for new ships, MEPC.212(63), represent a major step forward in implementing energy efficiency regulations for ships, MEPC.203(62), through the introduction of specifications for calculating the Energy Efficiency Design Index for various types of ships. There are, however, concerns regarding the sufficiency of propulsion power and steering devices to maintain manoeuvrability of ships in adverse conditions, hence safety of ships, if the Energy Efficiency Design Index requirements are achieved by simply reducing the installed engine power. In the frame of a review of current Energy Efficiency Design Index provisions, the paper discusses possible criteria required to ensure ship's manoeuvrability and safety under adverse conditions and proposes a way ahead regarding the implementation of these criteria by numerical methods and model tests.